PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA GURU PADA SMK â€œXYâ€ KOTA PEKANBARU - Dewita, Riska Afriani; Yapentra, Arhipen (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This article is the result of co-research the author and students in completing her final education at STIE Riau. The purpose of this research is to study and analyze influence of Supervision toward the Work Discipline of Teachers in the Vocational High School "XY" Pekanbaru. Respondents in this study amounted to 42 teachers and in its presentation the authors describe the descriptive and quantitative methods. Based on the results of data processing using the SPSS application, the t test results in simple linear regression obtained t_count > t_table (8.277> 2.020) and the significance value obtained 0.000 < 0.05. In connection with positive and significant supervision of the Work Discipline, Teachers with a contribution of 45.6%, based on the R Square Value obtained by 0.456 or 45.6%